Synthesis, Unidirectional Growth, Optical and Conductivity Studies of Single Crystals of L-Tartaric Acid - Ramesh Kumar, P.; Kumararaman, S.; Sagayaraj, P. (Asian Journal of Chemistry, 2010)
Oriented organic crystals along prerequisite direction are very important in terms of reducing loss of material and cost during nonlinear optical device fabrication. The L-tartaric acid single crystal was successfully grown by unidirectional modified Sankaranarayanan-Ramasamy method at ambient temperature for the first time and the growth conditions are optimized. The grown single crystal has been subjected to different characterization analyses in order to find out its suitability for device fabrication. The optical properties of the Sankaranarayanan-Ramasamy method grown crystal are found to be better than the crystal grown by the conventional slow solvent evaporation technique. The AC conductivity and dielectric studies are carried out for the grown crystal.